تعزيز العدالة الاجتماعية من خلال التركيز على الحقوق الفردية فى ضوء السنة والسيرة النبوية: Promotion of Social justice by forcing on individual rights in light of the Sunnah and Seerah - دكتور سید عبدالغفار بخاری (Al Manhal Research Journal, 2022)
This study explores the promotion of social justice through a focus on individual rights within the framework of the Sunnah (traditions) and Seerah (biography) of the Prophet Muhammad (peace be upon him). Social justice is a fundamental concept in Islam, reflecting the values of fairness and equity advocated by the Prophet. In this context, the study sheds light on several aspects of achieving social justice by emphasizing individual rights based on Islamic teachings. One of these aspects is the equal treatment of individuals under the law, as the Prophet Muhammad (peace be upon him) called for non-discrimination based on race, color, or nationality. The study also underscores the importance of protecting individual rights in areas such as property rights, freedom of expression, labor rights, education, healthcare, and political participation. The Prophet's life serves as an exemplary model that encourages respect for individual rights and fosters social justice. Furthermore, the study highlights the role of society and government in promoting social justice by safeguarding individual rights and providing equal opportunities for all. Social and economic initiatives can play a significant role in achieving this goal. In conclusion, focusing on individual rights in light of the Sunnah and Seerah of the Prophet Muhammad (peace be upon him) can be an effective means to promote social justice in Islamic societies. This approach contributes to greater balance and enhanced fairness across various social, economic, and political aspects of life.